2018
DOI: 10.15406/jmen.2018.06.00213
|View full text |Cite
|
Sign up to set email alerts
|

Combating diarrhoea in Nigeria: the way forward

Abstract: The Millennium Development Goals (MDGs) calls for a reduction of child mortality by two third between 1990 and 2015, the reality is that although progress is been made, much more remains to be done. The prevalence rate of diarrhoea in Nigeria is 18.8% and is a menace in sub-Sahara Africa; and in this part of West African it accounts for an estimated 150,000 deaths yearly amongst children under five due to poor hygienic and sanitary practices. Diarrhoea's status as the second leading killer of children under fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…Diarrhoea is a gastrointestinal condition caused by bacteria, virus and parasitic organisms (Peter & Umar 2018). It is characterised by increased intestinal motility, secretion and/or a decrease in the reabsorption of fluid and electrolytes (Ezeja et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diarrhoea is a gastrointestinal condition caused by bacteria, virus and parasitic organisms (Peter & Umar 2018). It is characterised by increased intestinal motility, secretion and/or a decrease in the reabsorption of fluid and electrolytes (Ezeja et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is characterised by increased intestinal motility, secretion and/or a decrease in the reabsorption of fluid and electrolytes (Ezeja et al 2012). More than half of diarrhoeal cases are reported in Africa and South Asia with a resultant mortality (Peter & Umar 2018). The incidence of diarrhoeal diseases varies greatly by seasons and age with children within the first 18 months of life being the most vulnerable (Peter & Umar 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite global success in the reduction of all cause and diarrhoea-specific mortality in the past 30 years, diarrhoea remains the second leading cause of death due to infections among children fewer than five years of age worldwide [2]. It is estimated that diarrhoea accounted for 9•9% of the 6•9 million deaths among children under 5 in 2011 [3,4], and it has been reported that the prevalence rate of diarrhoea in Nigeria is 18.8%; which is a menace in sub-Sahara Africa [5].…”
Section: Introductionmentioning
confidence: 99%